A pooled analysis of the association between sarcopenia and osteoporosis. Issue 46 (18th November 2022) - Yu, Xiaochao; Sun, Shuo; Zhang, Shaoxiong; Hao, Qinggang; Zhu, Boheng; Teng, Yirong; Long, Qing; Li, Shujun; Lv, Yan; Yue, Qiaoning; Lu, Sheng; Teng, Zhaowei
Abstract : Background: Sarcopenia is a progressive generalized skeletal muscle disorder that causes the accelerated loss of muscle mass and function. Osteoporosis is a systemic condition of the skeleton that results in low bone mass and quality. Several studies have suggested that osteoporosis and sarcopenia are interrelated; however, a few studies indicate the lack of a significant association between sarcopenia and osteoporosis. We aimed to evaluate the association between sarcopenia and osteoporosis via a systematic review and pooled analysis. Methods: From the inception of the PubMed and Embase databases until September 2022, we conducted a systematic search for studies evaluating the relationship between sarcopenia and osteoporosis. Study appraisal and synthesis methods: We included observational studies that provided 95% confidence intervals (CIs) and risk estimates. Two reviewers independently extracted data and assessed the quality of the research. The random-effects model was applied to the pool analysis, and the odds ratios (ORs) and 95% CIs were finally calculated. Results: The primary statistic was the mutual risk between sarcopenia and osteoporosis. According to the inclusion criteria, 56 studies (796, 914 participants) were finally included. Sarcopenia was significantly correlative to the risk of osteoporosis (OR, 3.06; 95% CI, 2.30–4.08), and each standard deviation increase in relative appendicular skeletal muscle mass was significantly related to a decreased risk of osteoporosis (OR, 0.65; 95% CI, 0.56–0.75). Osteoporosis observably referred to a higher risk of sarcopenia (OR, 2.63; 95% CI, 1.98–3.49). Conclusion: Our research indicated that sarcopenia and osteoporosis are highly positively correlated. Osteoporosis is closely associated with the risk of sarcopenia. Our finding highlights the importance of sarcopenia screening for those at risk of osteoporosis, and vice versa. However, heterogeneity was noted among the studies, and this might have influenced the accuracy of the results. Therefore, the results of our study should be interpreted with caution.